KAJIAN YURIDIS PIDANA DENDA TERHADAP KEKERASAN SEKSUAL PADA ANAK DIBAWAH UMUR - Amalia Pratiwi, Nisha; Sudantra, I Ketut (Kertha Wicara : Journal Ilmu Hukum; Vol. 02, No. 02, April 2013)
Penalty of fines is a payment of some amount of money from the convicted person based on the decision of the court. In history, penalty of fines has been used in the criminal law for centuries. At first, Anglo Saxons used financial punishment for the criminal systematically. Money payment as the indemnity is given to the victim. Setting and the way of application of the penalty of fines may vary according to conditions and development of society. And nowadays we know that all the penalty of fines payment that has been settled by the judge will be conferred to state cash. It is therefore this writing will discuss about how far is the concern of this country in protecting children from the sexual abasement and how is the utilization of the fine that is regulated in the law of children protection.
Keywords: Pinalty of Fince, Financial, Seexual Abuse, Children Protection